Keramikken fra Kragelund - Jessen, Ann Birgitte (Hikuin, 2001)
The pottery from Kragelund By Anne Birgitte Jessen The pottery from the kiln and the waster pit from Kragelund come from at least 54 vessels primarily of the types, pitcher, pot and bowl. All the vessel types are mainly coil built . The pitchers however are hand built up to the shoulder, after which the neck and the rim are thrown. The decoration is simple. On the pitchers occur horizontal grooves (often in pairs) placed in such a way that they accentuate changes in the shape of the pitcher. In addition to the horizontal grooves painted stripes of iron oxide and applied and raised motifs resembling raspberries occur. Pots and bowls are decorated with horizontal grooves right below the rim. In a few cases an undulating line occurs below the grooves. Glaze only occurs on pitchers, but unglazed pitchers are represented as well. The very common form and decoration types that characterize the pottery from Kragelund do not allow a narrow dating. The kiln seems to have functioned for a short period of time in the 14th century.